Potential location for installation of ANPR by using GIS-AHP / Muhammad Ariff Iskandar Abdul Razak, Maisarah Abdul Halim and Nabilah Naharudin - Abdul Razak, Muhammad Ariff Iskandar; Abdul Halim, Maisarah; Naharudin, Nabilah (College of Built Environment, 2023)
This study is to determine potential installation on ANPR using AHP and GIS in Kuala Lumpur.